The role of teachers' creativity in higher education: a systematic literature review and guidance for future research - Han, Weijing; Abdrahim, Nur Aira (Elsevier, 2023)
Creativity plays an important role in education. All around the world, educational institutes are calling for teachers to implement a shift from traditional pedagogy to be more creative (Cropley & Patston, 2019; Renzulli, 2017), and to apply creativity in their teaching activities (Narayanan, 2018). However, teachers are often thought of as resistant and slow to change (Ellis & Childs, 2019). This study constitutes a systematic literature review using the PRISMA approach to trace the research on teachers’ creativity in higher education. The study defined the concept of creativity within the higher educational domain, identified its significance, and determined its influencing factors. The results obtained indicate that teachers’ creativity plays a critical role in developing students’ competence and teachers’ professional development. Teachers’ creativity is the result of the interaction between personal characteristics and the surrounding social environment. The outcomes of this review will benefit teachers in helping them understand the meaning of creativity as well as in figuring out its most influential factors and challenges in order to better achieve its goals.